Fat mass and fat‐free mass track from infancy to childhood: New insights in body composition programming in early life. Issue 11 (21st September 2021) - van Beijsterveldt, Inge A. L. P.; de Fluiter, Kirsten S.; Breij, Laura M.; van der Steen, Manouk; Hokken‐Koelega, Anita C. S.
Abstract: Objective: Early life is a critical window for adiposity programming. This study investigated whether fat mass percentage (FM%), fat mass index (FMI), abdominal fat, and fat‐free mass (FFM) in early life track into childhood and whether there are sex differences and differences between infant feeding types. Methods: Detailed body composition was longitudinally measured by air‐displacement plethysmography, dual‐energy x‐ray absorptiometry, and abdominal ultrasound in 224 healthy, term‐born children. Measurements were divided into tertiles. Odds ratios (OR) of remaining in the highest tertile of FM%, FMI, abdominal subcutaneous and visceral fat, and FFM index (FFMI) were calculated from early life to age 4 years. Results: High FM% and FMI tracked from age 3 and 6 months to age 4 years (OR = 4.34 [ p = 0.002] and OR = 6.54 [ p < 0.001]). High subcutaneous abdominal fat tracked from age 6 months to age 4 years (OR = 2.30 [ p = 0.012]). High FFMI tracked from age 1, 3, and 6 months to age 4 years (OR = 4.16 [ p = 0.005], 3.71 [ p = 0.004], and 3.36 [ p = 0.019]). In non‐exclusively breastfed infants, high FM% tracked from early life to age 4 years, whereas this was not the case for exclusively breastfed infants. There was no tracking in visceral fat or sex differences. Conclusions: Infants with high FM%, FMI, subcutaneous abdominal fat, and FFMI in early life are likely to remain in the highest tertile at age 4 years. Exclusive breastfeeding for 3 months is potentially protective against having high FM% at age 4 years.